THE EFFECT OF SMALL GROUP DISCUSSION TECHNIQUE ON THEABILITY OF THE SECOND YEAR STUDENTS OF SMP N 5 KERINCIKANAN IN COMPREHENDING REPORT TEXTS - Asmawati, Lia; Jismulatif, Jismulatif; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The aim of this research was to find out the effect of Small Group Discusstion Technique on the Ability of the Second Year Students of SMP N 5 Kerinci Kanan in Comprehending Report Texts. There were 98 population and only 32 students as the sample through cluster random sampling technique, instead cluster random sampling allows the writer to collect data into small, more effective groups. The test was carried out as pre-test. The treatment was applied by using small group discussion in reading report text and post-test. In order to know the difference between pre-test and post-test, and to test the hypothesis, t-test formula was used. After analyzing the data, it was found that t-test score was 21.326 which t-table score in significance level df=32 was 0.349. Since t-test was higher than t-table, it can be concluded that alternative hypothesis was accepted. In other word, it can be restated that small group discussion can help students to improve their reading ability especially in report text. The implication of the finding is that the students should maximize the practice of small group discussion.Key Words: Effect, Small Group Discussion, Report Text